Structural and Functional Changes of Carotid Wall Properties in Patients with Acromegaly are not Restored after 1 year of GH/IGF1 Normalization - Găloiu, S.; Jurcuţ, R.; Vlădaia, A.; Florian, A.; Purice, M.; Popescu, B. A.; Ginghină, C.; Coculescu, M. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Vascular changes are common in acromegaly (ACM). Current therapies can normalise the levels of both growth hormone (GH) and insulin-like growth factor (IGF1).To establish whether the ACM vascular changes in patients with effectively managed disease are different from those in patients with an active condition.64 ACM patients were tested for serum GH (random and during an oral glucose tolerance test) and IGF1. Ultrasonography of the right common carotid (RCC) explored structural (the carotid diameter and intima-media thickness index (IMT)) and functional (the augmentation index (AIx), elastic modulus (Ep), and local pulse wave velocity (PWV)) arterial parameters in the ACM patients (groups A and B) and an age- and sex-matched control group of 21 patients without acromegaly (group C).The ACM patients were divided into 2 subgroups that had similar cardiovascular risk factor profiles: A (n=10, with controlled ACM), and B (n=54, with active ACM). The AIx was higher in groups A (27.7% [2.2–54.3]) and B (20.0% [ − 38.2–97.1]) than in group C (3.5% [ − 11.3–31.1]), p=0.01 and 0.002, respectively. The group B patients presented with poorer functional carotid wall parameters than the control subjects: Ep-95.5 [33–280] KPa vs. 77.5 [39–146] KPa, p=0.01; and PWV-6 [3.6–10.4] m/s vs. 5.4 [3.9–7.2] m/s, p=0.03.The ACM patients had greater RCC diameters (6.4±0.6 mm vs. 5.7±0.6 mm, p<0.001) and IMT values (0.72±0.13 mm vs. 0.58±0.08 mm, p<0.001) than the subjects in group C.Both the controlled and active ACM patients showed structural arterial changes. After 1 year of disease control, the patients with controlled ACM showed improvements in the functional, but not the structural, arterial parameters compared with the patients with an active condition.
Keywords: pituitary adenoma; cardiovascular risk management; GH adrenal gland